Late-Onset CLCN2-Related Leukodystrophy Associated With A Novel Mutation - Pikija, Slaven; Feige, Julia; Toma, Andreea; Radlberger, Richard; Trinka, Eugen; Klausner, Fritz; Safdarian, Mahdi (Journal of Neurology Research, 2025)
Loss-of-function mutations in the chloride channel protein 2 (CLCN2) gene cause defective channel function, leading to a specific type of leukodystrophy named CLCN2-related leukoencephalopathy. This is a rare disease that can become apparent either in childhood or adulthood but generally does not progress significantly. Here, we present an infertile man in his 60s with genetically confirmed novel homozygotic CLCN2 mutation and typical magnetic resonance imaging (MRI) findings of leukodystrophy who presented with severe headache to our clinic. The patient had no other specific neurologic findings, and we believe he is the oldest case reported in the literature with genetically confirmed diagnosis of CLCN2-related leukodystrophy.